Application of the Sad Kerthi Concept in Developing Marine Tourism Area on the Blue Economy in Karangasem Regency - Osin, Rosvita Flaviana; Putra, I Nyoman Darma; Sudiarta, I Nyoman; Sari, Ni Putu Ratna (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2025)
This study presents a problem statement by exploring the application of the Sad Kerthi concept in the development of a marine tourism area in Karangasem Regency, Bali, with a focus on blue economy principles. The Sad Kerthi, deeply rooted in Balinese Hindu local wisdom, emphasizes the preservation of six sacred elements: Atma (soul), Segara (ocean), Danu (lake), Wana (forest), Jagat (earth), and Jana (human). The challenge lies in applying the blue economy approach to optimize the sustainable and wise utilization of marine resources while maintaining ecosystem balance and enhancing local community welfare. By aligning with Blue Economy principles, which advocate for the sustainable use of ocean resources for economic growth, the study underscores the potential of integrating traditional wisdom with modern economic models. The research indicates a methodology that utilizes a qualitative approach, conducting in-depth interviews with experts from governmental and cultural sectors, as well as academic and research programs that incorporate these values of local wisdom. The main findings indicate that local wisdom and the blue economy are interdependent, mutually strengthening each other in the quest for sustainable development. Local wisdom serves as a cornerstone for sustainable practices, cultural values, and community involvement, which can significantly enhance the effectiveness of the Blue Economy framework. The main conclusions of this research contribute to the discussion on sustainable tourism by illustrating the effectiveness of a culturally rooted approach to achieving both environmental and economic sustainability.